2016
DOI: 10.1186/s12978-016-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

A community-based study on prevalence and correlates of erectile dysfunction among Kinondoni District Residents, Dar Es Salaam, Tanzania

Abstract: BackgroundGlobally, erectile dysfunction burden (ED) is rising appreciably and it is projected to affect about 332 million men by the year 2025. This rise is attributable to the rising incidence of conditions associated with ED including obesity, diabetes, hypertension, coronary artery disease and depression. We conducted this community-based screening to elucidate on the prevalence of ED and its associated factors among men residing in an urban community in Tanzania.MethodsWe conducted a cross-sectional commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 70 publications
5
52
0
1
Order By: Relevance
“…Age as a risk factor for ED was universal across all studies. A linear relationship between increasing ED prevalence and increasing age was also seen in all studies, regardless of the ED assessment method used [5,9,[13][14][15][16][18][19][20][21][22][23][24][25][26]29,[31][32][33][34]38,[41][42][43][44][45]48]. Physiological ageing processes mediating vascular changes in the penis have been implicated; however, cardiovascular comorbidities, such as diabetes and HTN, appear to expedite and exacerbate the process [67].…”
Section: Ed and Agementioning
confidence: 92%
See 2 more Smart Citations
“…Age as a risk factor for ED was universal across all studies. A linear relationship between increasing ED prevalence and increasing age was also seen in all studies, regardless of the ED assessment method used [5,9,[13][14][15][16][18][19][20][21][22][23][24][25][26]29,[31][32][33][34]38,[41][42][43][44][45]48]. Physiological ageing processes mediating vascular changes in the penis have been implicated; however, cardiovascular comorbidities, such as diabetes and HTN, appear to expedite and exacerbate the process [67].…”
Section: Ed and Agementioning
confidence: 92%
“…Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] shows the prevalence of ED assessed by the IIEF, IIEF-5 or IIEF variants. The overall global prevalence was 13.1-71.2% [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The prevalence by continent was as follows: North America, 20.7% [17]; Europe, 16.8-65.4% [22,23,26,27]; Oceania, 40.3-42% [13,16]; Asia, 13.1-71.2% [14,18,19,21,24,25]; and Africa, 24-58.9% [15,20].…”
Section: Ed Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that alteration of the cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway among men with diabetes with impaired vascular relaxation is related to endothelial dysfunction (16)(17)(18). Among men with diabetes, risk factors include increasing age, duration of diabetes, poor glycemic control, cigarette smoking, hypertension, dyslipidemia, androgen-deficiency states (19) and cardiovascular disease (CVD) (6,11,12,(20)(21)(22)(23)(24).…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…In addition, studies indicate that 40% of men with diabetes greater than 60 years of age have complete ED (7-15).Recent studies have reported that alteration of the cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway among men with diabetes with impaired vascular relaxation is related to endothelial dysfunction (16-18). Among men with diabetes, risk factors include increasing age, duration of diabetes, poor glycemic control, cigarette smoking, hypertension, dyslipidemia, androgen-deficiency states (19) and cardiovascular disease (CVD) (6,11,12,(20)(21)(22)(23)(24).ED as a marker of potential cardiovascular (CV) events has been reported by numerous investigators (25-34). In fact, ED has been shown to be significantly associated with all-cause mortality and CV events (35)(36)(37).…”
mentioning
confidence: 99%